Pattern and spectrum of tornado injury and its geographical information system distribution in Yancheng, China: a cross-sectional study - Deng, Qiangyu (BMJ Open, 2018)
OBJECTIVES: Few studies of tornado injuries have considered differences related to damage levels and Enhanced-Fujita (EF) scale ratings. This study aimed to evaluate the pattern, spectrum and geographical distribution of injuries related to the Yancheng tornado and provide guidelines for effective emergency medical strategies. SETTING: The study was conducted at three hospitals which treated patients with injuries related to the tornado in Yancheng, China. PARTICIPANTS: We obtained the records of 451 patients with tornado-related injuries. Of these, 401 valid trauma medical records were included; 50 other records were excluded for insufficient information. Informed consent was obtained from all patients by telephone. MAIN OUTCOME MEASURES: We analysed patients’ injury sites and types and used the abbreviated injury scale (AIS) to standardise injury severity. Geographical information system and non-parametric tests were used to analyse the effects of geographical factors on casualties. RESULTS: Women, middle-aged/elderly individuals (age>45 years) and children/adolescents (<18 years) accounted for 51.62%, 77.30% and 12.47% of injured patients, respectively. This caused a dumbbell-shaped age distribution. Head (46.63%), body surface (39.90%) and lower-limb (29.43%) injuries were common, as were soft-tissue injuries (90.77%), fractures (38.90%) and organ damage (19.70%). Minor injuries (AIS=1) were common (60.85%), whereas critical/fatal injuries (AIS≥5) were very rare (2.50%). Although the densities of injury varied among damage levels and EF ratings for different areas, area-wise differences in injury severity (AIS scores) were not significant (p>0.05). CONCLUSION: We recommend the use of helmets to prevent head injuries caused by tornadoes and suggest prioritising the treatment of high-risk head and multiple-organ injuries. Additionally, medical rescuers should follow the ‘same quality and different quantity’ principle: the injured in all affected areas should receive equal attention, but numbers of medical personnel should be allocated based on the level of effects from the tornado.